The Evaluation of Marketing Mix Elements: A Case Study - Thabit H. Thabit; Manaf B. Raewf (International Journal of Social Sciences & Educational Studies, 2018)
The paper aims to investigate the influencing of marketing mix (MM) elements (product, price, place or distribution, and promotion) on increasing the effectiveness of product promotion and their role to reduce the problems within the organization. The main importance aspects of this paper are to discuss the theoretical part of MM, to provide some perspectives for the researchers, and to give some instructions for the marketing department in Al-Saaeda Company for medical equipment technologies. The researchers used the main related academic resources from university library, and internet, and they designed and distributed questionnaires on a random sample of Al-Saaeda Company for Medical Equipment Technologies customers and the company employees to measure the impact of promotion on the marketing of its product (Glucocard 01-mini plus). The main findings of this paper can be concluded as following: 1. The promotion has a very high level of impact to increase the sales of products. 2. The good distribution of product can effect positively on customer satisfaction. 3. The company’s policy for promoting has a very good reflection on increasing the sales of products. The researchers recommended that the company must strengthen the level of promotions in its activities and departments, and the increasing of sales points is very important, so the company must enhance its policies of distribution.